Combined early treatment in hemiplegic attacks related to CACNA1A encephalopathy with brain oedema: Blocking the cascade?. (October 2017) - Camia, Francesca; Pisciotta, Livia; Morana, Giovanni; Schiaffino, Maria Cristina; Renna, Salvatore; Carrera, Paola; Ferrari, Maurizio; Baglietto, Maria Giuseppina; Veneselli, Edvige; Siri, Laura; Mancardi, Maria Margherita
Introduction: Variants in the CACNA1A gene on chromosome 19p13 result in a spectrum of neurological phenotypes ranging from familial or sporadic hemiplegic migraine to congenital or progressive encephalopathies. Patients with CACNA1A variants often show acute attacks with ataxia or hemiplegia till coma, sometimes related to unilateral brain oedema. No guidelines for the medical management of these attacks are available since treatment is empiric, and many cases do not respond to common antimigraine drugs. Case description: We report on the emergency personalized treatment protocol used in an 11 year-old girl with CACNA1A-related encephalopathy for the management of acute attacks of headache, hemiconvulsions and hemiplegia with coma. Discussion: Combined corticosteroid pulses and hypertonic solution led to a reduction in severity and duration of acute attacks when administered in the early stages, characterized by migraine, seizure, fever, vomiting and impairment of consciousness associated to hemispheric slowing on the EEG.